Loneliness, Circulating Endocannabinoid Concentrations, and Grief Trajectories in Bereaved Older Adults: A Longitudinal Study - Kang, Minhi; Bohorquez-Montoya, Luisa; McAuliffe, Timothy; Claesges, Stacy A.; Blair, Nutta-On; Sauber, Garrett; Reynolds, Charles F.; Hillard, Cecilia J.; Goveas, Joseph S. (Frontiers in Psychiatry, 2021)
Background. Loneliness is one of the most distressing grief symptoms and is associated with adverse mental health in bereaved older adults. The endocannabinoid signaling (ECS) system is stress-responsive and circulating endocannabinoid (eCB) concentrations are elevated following bereavement. This study examined the association between loneliness and circulating eCB concentrations in grieving older adults and explored the role of eCBs on the association between baseline loneliness and grief symptom trajectories. Methods. A total of 64 adults (grief with high loneliness: n=18; grief with low loneliness: n=26; and healthy comparison [HC]: n=20) completed baseline clinical assessments for the UCLA loneliness scale. In grief participants, longitudinal clinical assessments, including the Inventory of Complicated Grief and 17-item Hamilton Depression Rating scales, were collected over six months. Baseline circulating eCB (N-arachidonoylethanolamine [AEA] and 2-arachidonoylglycerol [2-AG]) concentrations were quantified in the serum using isotope dilution, liquid chromatography-mass spectrometry; cortisol concentrations were measured in the same samples using radioimmunoassay. Results. Circulating AEA concentrations were higher in severely lonely grieving elders than in HC group; cortisol concentrations were not different among the groups. Cross-sectionally, loneliness scores were positively associated with AEA concentrations in grievers; this finding was not significant after accounting for depressive symptom severity. Grieving individuals who endorsed high loneliness and had higher 2-AG concentrations at baseline showed faster grief symptom resolution. Conclusions. These novel findings suggest that in lonely, bereaved elders, increased circulating eCBs, a reflection of an efficient ECS system, are associated with better adaptation to bereavement. Circulating eCBs as potential moderators and mediators of the loneliness-grief trajectory associations should be investigated.